Pengaruh Perilaku Konsumen Terhadap Keputusan Pembelian Asuransi Pendidikan (Studi Kasus Pada PT Sunlife Financial Cabang Medan) - Indah Rayansi; Rahmi Rayansi (Jurnal Manajemen Akuntansi (JUMSI), 2022)
The problem studied in this study is about the purchase of Education Insurance which has fluctuated in the last 5 years (2017-2021) caused by a decrease in customers who buy education Insurance from year to year and a decrease in customers who extend the purchase of Education Insurance policies. This study aims to determine the effect of consumer behavior on purchasing decisions Education Insurance at PT. Sunlife Financial Insurance Medan branch. This study uses a quantitative approach and uses primary data by distributing questionnaires to 100 customers as a sample with a population of 100 customers, the sampling technique using the Slovin formula with Likert Scale measurements. The data is processed through SPSS V 20.0 program with technical simple linear regression analysis. The results showed that here was a positive and significant influence of consumer behavior on the purchase decision of Education Insurance at PT. Sunlife Financial Insurance Medan Branch from the results of the t test partially proves that consumer behavior variables affect purchasing decisions with tcount 8.581 > t table 1.66055 and the significance value is less than 0.05, which is 0.000.